Blood Pressure Variability and Cerebral Small Vessel Disease: A Systematic Review and Meta-Analysis of Population-Based Cohorts. Issue 1 (January 2020) - Ma, Yuan; Song, Alex; Viswanathan, Anand; Blacker, Deborah; Vernooij, Meike W.; Hofman, Albert; Papatheodorou, Stefania
Abstract : Background and Purpose—: Blood pressure (BP) variability may increase the risk of stroke and dementia. It remains inconclusive whether BP variability is associated with cerebral small vessel disease, a common and potentially devastating subclinical disease that contributes significantly to both stroke and dementia. Methods—: A systematic review and meta-analysis of prospective cohort studies that examined the association between BP variability and the presence or progression of established markers of cerebral small vessel disease, including white matter hyperintensities, lacunes, and microbleeds on magnetic resonance imaging. We searched MEDLINE, EMBASE, and Web of Science. Ten studies met the criteria for qualitative synthesis and 7 could be included in the meta-analysis. Data were synthetized using random-effect models. Results—: These studies included a total of 2796 individuals aged 74 (mean) ±4 (SD) years, with a median follow-up of 4.0 years. A one SD increase in systolic BP variability was associated with increased odds of the presence or progression of white matter hyperintensities (odds ratio, 1.26 [95% CI, 1.06–1.50]). The association of systolic BP variability with the presence of lacunes (odds ratio, 0.93 [95% CI, 0.74–1.16]) and the presence of microbleeds (odds ratio, 1.13 [95% CI, 0.89–1.44]) were not statistically significant. Conclusions—: A larger BP variability may be associated with a higher risk of having a higher burden of white matter hyperintensities. Targeting large BP variability has the potential to prevent cerebral small vessel disease and thereby reducing the risk of stroke and dementia. The potential issue of reverse causation and the heterogeneity in the assessment of cerebral small vessel disease markers should be better addressed in future studies. Abstract : Supplemental Digital Content is available in the text.